1994
DOI: 10.1002/ajhb.1310060212
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of body fat and body fat distribution in 11‐year‐old children using magnetic resonance imaging and hydrostatic weighing, skinfolds, and anthropometry

Abstract: From early pubescence, both degree and distribution of fatness have been related to health risk factors. Measures that are capable of providing estimates of overall fatness and the extent of high risk fat patterning are, therefore, advantageous. The objective of this study was to compare estimates of body fatness and fat distribution using magnetic resonance imaging with the traditional methods of hydrostatic weighing, skinfolds, and anthropometry in 11-year-old boys and girls. Subjects were 25 boys and 25 gir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Body breadths were measured at the biacromial and bitrochanteric sites using a sliding beam anthropometer. The same skinfold, girth and circumference combinations, including sum of skinfolds, trunk to limb ratios, waist ± hip circumference ratio (WHR) were used as in the previous study 9,10 to assess fat distribution. These combinations were selected from suggestions from previous research assessing childrens' fat distribution.…”
Section: Skinfolds Anthropometry and Maturationmentioning
confidence: 99%
See 1 more Smart Citation
“…Body breadths were measured at the biacromial and bitrochanteric sites using a sliding beam anthropometer. The same skinfold, girth and circumference combinations, including sum of skinfolds, trunk to limb ratios, waist ± hip circumference ratio (WHR) were used as in the previous study 9,10 to assess fat distribution. These combinations were selected from suggestions from previous research assessing childrens' fat distribution.…”
Section: Skinfolds Anthropometry and Maturationmentioning
confidence: 99%
“…It has provided reliable estimates of intra-abdominal fat and subcutaneous fat areas in transverse scans and recently, with a sample of men, multiple scans have shown promise in the estimation of fat volumes. 5 Progress has been made using CT or MRI with the estimation of intra-abdominal fat in pre-pubertal children, 6 ± 8 early pubertal children, 9,10 and adolescents. 3,11 These studies, although few in number, have provided the ®rst assessments of the degree and nature of intra-abdominal deposition in children.…”
Section: Introductionmentioning
confidence: 99%
“…There is no agreement about the side of the body from which anthropometric measurements must be obtained. In general, in Europe Deurenberg et al, 1990Deurenberg et al, ,1999Gurrici et al, 1998) and in children (Tanner & Whitehouse, 1962,1975Gerver & de Brain, 1996;Moreno et al, 1998;Paul et al, 1998), we choose the left side of the body, and in sports medicine (Peters et al, 1994;Eliakim et al, 1997;Katzmarzyk et al, 1999) and in North America (Johnston et al, 1988;Must et al, 1991;Sangi & Mueller, 1991), the right side of the body is used. Some papers even show data from both sides (Lean et al, 1996) and others use the non-dominant side of each individual (Barker et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…In Portuguese children of about the same age as ours, Teixeira et al (25) indicated that the sum of three trunk skinfolds was highly (p < 0.001) related to total trunk fat mass measured using DXA. In comparison, Peters et al (26) using MRI indicated that the horizontal abdominal skinfold had a strongest correlation with total body fat in girls. Mesomorphy, which mirrors the developmental stage of the musculo-skeletal systems from the somatotype components, characterized 35% of the body impedance in boys (see Table 3).…”
Section: Discussionmentioning
confidence: 94%